Disrupted copresence: Older adults' views on mobile phone use during face-to-face interactions. (September 2018) - Kadylak, Travis; Makki, Taj W.; Francis, Jessica; Cotten, Shelia R.; Rikard, R. V.; Sah, Young June
This study investigates older adults' perceptions of mobile phone use during face-to-face interactions and social gatherings. Data were derived from 9 semistructured focus group interviews. Study participants were older adult residents of Michigan, US ( N = 77). Focus groups were held in both urban and rural locations and our sample was heterogeneous in terms of race and socioeconomic status. Older adults in this study reported that the mobile phone behavior displayed by their younger family members during face-to-face interactions and family gatherings breaches their expectations regarding appropriate etiquette and manners. Specifically, participants reported they view mobile phone use during face-to-face interactions as disruptive to communication quality, offensive, and a potential signal of inattention, which may curtail intergenerational communication and hinder their sense of copresence. Limitations of our study and directions for future research are discussed.